Latitudinal variation in the prevalence of multiple sclerosis in Ireland, an effect of genetic diversity. Issue 4 (16th March 2004) - McGuigan, C; McCarthy, A; Quigley, C; Bannan, L; Hawkins, S A; Hutchinson, M
Abstract : Background: Northern Ireland has a high and rising prevalence rate of multiple sclerosis (MS). The most recent survey in 1996 found a rate of 168.7/100 000. Recorded prevalence rates for the south of Ireland, including County Wexford, have been markedly lower and seemed to suggest the existence of a prevalence gradient within the island. Objectives: To compare the prevalence of multiple sclerosis in Co. Wexford in the south east of Ireland and Co. Donegal in the north west, and to establish whether a variation in prevalence of MS exists within Ireland. Methods: Patients were referred from multiple sources. Review of clinical case records and/or patient examination confirmed the diagnosis. Results: In Co. Wexford, 126 patients were found to have clinically definite or probable multiple sclerosis with a prevalence rate of 120.7/100 000 (95% confidence intervals (CI) 100.6 to 143.8), which is similar to other areas of similar latitude within the British Isles. In Co. Donegal, 240 people had clinically definite or probable MS with a prevalence rate of 184.6/100 000 (95% CI 162.0 to 209.5). The difference in prevalence rates is statistically significant (Z = 3.94, p = <0.001). Conclusion: There is a latitudinal variation in the prevalence rate of MS between the north and the south of Ireland. The increased prevalence of MS seen in Co. Wexford is likely to represent better case ascertainment and improved diagnostic accuracy rather than an actual increase in prevalence. The north/south variation in prevalence may represent a variation in the genetic predisposition to MS between the background populations of the two counties.